Primary histiocytic sarcoma in the brain with renal metastasis causing internal ophthalmoparesis and external ophthalmoplegia in a Maine Coon cat. Issue 2 (August 2021) - Monteiro, Susana; Hughes, Katherine; Genain, Marie-Aude; Alves, Lisa
Case summary: An 11-year-old neutered male Maine Coon cat was presented for investigation of anisocoria and depression. Neurological examination was consistent with a lesion at the level of the middle cranial fossa, and biochemistry was indicative of moderate renal functional impairment. MRI of the brain identified an extra-axial mass lesion at the level of the middle cranial fossa, T2-weighted hyperintense and strongly homogeneously contrast enhancing with dural tail. The cat was euthanased after 6 weeks of palliative treatment with corticosteroids. Histopathology and immunohistochemistry of the brain, the intra-cranial mass and the renal masses found on necropsy were consistent with histiocytic sarcoma. Relevance and novel information: Central nervous system histiocytic sarcoma is a rare finding in cats. This original case report describes the neurological presentation, novel MRI characteristics and pathological findings of suspected primary histiocytic sarcoma affecting the brain with renal metastasis in a cat.